3D μ-printing of polytetrafluoroethylene microstructures: A route to superhydrophobic surfaces and devices. (June 2020) - Zhang, Yangxi; Yin, Ming-Jie; Ouyang, Xia; Zhang, A. Ping; Tam, Hwa-Yaw
Graphical abstract: Highlights: A 3D micro-printing technology is presented to fabricate 2D/3D PTFE microstructures to tap PTFE's unique properties for new applications. A route to fabricate large-area superhydrophobic surfaces via multiscale micro/nano-engineering of PTFE is established. 3D PTFE micro-scaffolds for direct and rapid formation of liquid droplet-based optical whispering-gallery-mode resonators are demonstrated. Biomimetic PTFE water strider that can carry weight more than 30 times its self-weight and be flexibly driven on water surface is demonstrated. Abstract: Polytetrafluoroethylene (PTFE) is a fluoropolymer well known for chemical inertness and insolubility, as well as the extreme hydrophobicity that can be achieved. Nonetheless, those unique properties make PTFE difficult to process, PTFE components are usually fabricated from the powder, and later shaped using traditional machining processes. So, although 3D printing can provide flexibility, fast and economically production of on-demand parts, especially complex 3D geometries that are hard or impossible to fabricate by machining processes, attempts to introduce PTFE into 3D printing are extremely rare and difficult. Here, we report a 3D micro-printing (μ-printing) method based on digital ultraviolet (UV) lithography for fabrication of micrometer-scale 3D PTFE structures and investigate their superhydrophobic properties and applications. In this method, PTFE nanoparticles are dispersed in a photocurable solution of polyethylene glycol diacrylate (PEGDA) and then 3D printed into predefined microstructures by layer-by-layer UV projection exposures. Subsequent sintering process removes other polymer with relatively low decomposition temperature to leave pure PTFE microstructure. In the experiments, 3D PTFE microscaffolds for droplet lasers and electrostatic-driven biomimetic water striders have been demonstrated to show the wide applications of the micro/nano-structured superhydrophobic PTFE surfaces as well as the flexible microengineering ability of the 3D μ-printing method.